Strength improvement by surcharge and vacuum preloading - Lew, Chloe Yan Bin Jmi (Nanyang Technological University, 2023)
This study used Kaolin as the sample material to examine the impact of vacuum and surcharge preloading on the undrained shear strength and soil-water characteristic curve of fine-grained soil. Consolidated kaolin samples were trimmed into cylindrical specimens and subjected to different pre-consolidation pressures. Soil specimens were tested to determine the stress-strain curves and undrained shear strength. The study also plotted SWCCs in terms of volumetric water content, gravimetric water content, and degree of saturation. The soil specimens' air-entry value was deduced from the plotted S- SWCC. The results showed that vacuum preloading significantly improved the undrained shear strength of the soil, and the strength improvement was more significant compared to surcharge preloading. The study suggests that further research should be performed to investigate the influence of vacuum consolidation on other fine-grained soils. Overall, the findings from this study provide valuable insights into the use of vacuum preloading to improve soil strength for various engineering applications.